Health Literacy and Written Communication in Skilled Nursing/Subacute Facilities. (April 2018) - Galati, Christopher; Adams, Rachel; Graham, Kay; Reynolds, Katharyn; Zametin, Julia
Health literacy is a concern for older adults. Low health literacy can lead to adverse health outcomes; therefore, practitioners should address health literacy with clients. There is limited research addressing occupational therapy (OT) practitioners' knowledge of health literacy and its implementation in written communication in skilled nursing facility (SNF)/subacute settings. Researchers explored practitioners' knowledge and current practices when using written communication with older adult clients in skilled nursing and subacute settings. This was a nonexperimental, descriptive study of OT practitioners using an online survey. OT practitioners reported having knowledge of health literacy and addressing health literacy with clients. Although knowledge and practice scores were higher for occupational therapy assistants than for occupational therapists, no reliable differences were noted between practitioners. Survey measures yielded good internal consistencies (Cronbach's α= 0.8). While the participants reported having knowledge and practice of health literacy, participants reported limited resources and training in this area.